The Effects of Compettion Market on The Implementation of Halal Food Standards - Toufik, Bedj Bejd (Al-Basirah Journal, 2018)
Halal Products as a subset of the whole Islamic teaching are immutably attached to a certain Halal Standards. The growing number of Muslim population that is more sensitive and concerned about the food that they consumed has generated strong economic opportunities for business communities over the world. Meanwhile, the acceptances of Halal label by Muslim consumers is due to the believe that the products is Shariah (Islamic laws) compliant. However, in competitive markets the profit motive play major role including others motives. Therefore, in the free market different key players must compete with each other under the market rules. Competitiveness in the markets will form under certain conditions, the most important is the price which can be controled by the rule of minimize the cost to maximize the profit. It is clear that the Halal standards engage additional costs, which are regarded by some players as not necessary cost . The objectives of this study are to provide greater understanding of the importance of implementation of Halal standards in increasing consumer demands in one hand, and from other hand to explain that some market players they are targeting higher profit from Halal market and they dont care if the products are Shariah compliant or not. Findings showed that The strict requirement of Halal standard makes the entry to this potential market often challenging for many players. Meanwhile, in which concern certefication, the study show that some market players prefer to use vicious ways to be certefied such as; falsfing Halal certeficate or get certefication from unqualified organisation, or even through shoping legal Halal label, than to follow Halal stnadards. The study show also, that the lack of institutional and human resources capacity, and the competition markets are the mean stone factors to contribute to the less strict implementation of Halal standards buy various agencies .